PENCIPTAAN TARI CALENGSAI KARYA RIANTO - Saputri, Willia Dwi; Kuncoro, Jonet Sri (Institut Seni Indonesia Surakarta, 2023)
The Calengsai Dance is a creative work born from the acronym of three cultural elements: Calung, Lengger, and Barongsai. This dance portrays the unique cultural journey between China and Banyumas, where the elements of Calung, Lengger, and Barongsai are crafted, developed, and acculturated into a harmonious unity. The result is the creation of a new dance work titled Calengsai Dance, which is performed in the Metamorphosis Lengger show. This dance is a form of development from the original work created by Sri Rahayu, which was further developed by Rianto. In its development process, Rianto added new elements such as Chinese singers, Barongan Banyumas, and dancers with buffalo heads known as pembarong. Through this innovation, the Calengsai Dance becomes not just a new creative dance but also a symbol of the acculturation of two great cultures, namely Javanese and Chinese. The presence of Calung Lengger, Barongsai, and Barongan Banyumas in this dance reflects a fusion of Banyumasan traditional movements, meticulously crafted by Rianto through processes of observation, exploration, experimentation, formation, and intensive training for the dancers. The final result of this process is a work of art that not only captivates aesthetically but is also rich in cultural values, embodying a dialogue between tradition and innovation in the contemporary dance scene of Indonesia.